A REVIEW OF RECENT REPORTS ON THE TREATMENT OF OSGOOD-SCHLATTER DISEASE - Mateusz Korga; Sylwia Koziej; Katarzyna Zych; Kornelia Rojek; Dominika Żyła; Michał Korona; Andrzej Zuzak; Jakub Jagiełło; Milena Krawczyk; Dominik Łepecki (International Journal of Innovative Technologies in Social Science, 2025)
Osgood-Schlatter disease (OSD) is a frequent cause of anterior knee pain in active adolescents, typically during rapid growth. It results from repetitive traction of the patellar tendon on the tibial tuberosity, causing inflammation and pain. The condition is usually self-limiting, resolving with skeletal maturity, though symptoms may persist into adulthood. This article provides an overview of OSD, including pathophysiology, clinical presentation, differential diagnosis, diagnostic methods, treatment, prognosis, and prevention.A key aspect is differentiating OSD from other causes of anterior knee pain, such as Sinding-Larsen-Johansson syndrome, Hoffa's fat pad syndrome, patellar tendon rupture, chondromalacia, tumours, tibial tubercle avulsion, and osteomyelitis. Diagnosis requires clinical evaluation supported by MRI or ultrasound. Studies indicate that risk factors like muscle tightness and altered biomechanics may contribute to OSD.Conservative management is first-line, involving rest, activity modification, cryotherapy, NSAIDs, and physiotherapy. In refractory cases, surgical methods—including arthroscopic or open techniques—may be considered. Novel approaches like platelet-rich plasma (PRP) therapy and nanoarthroscopy show encouraging outcomes.Prognosis is favourable, with most patients recovering by puberty, though some have persistent pain if diagnosis or treatment is delayed. Preventive strategies include gradual training progression, muscle strengthening and stretching, proper equipment, and monitoring young athletes.This review synthesises current evidence to support clinicians, physiotherapists, and sports medicine professionals in managing OSD.